The OntoNL Semantic Relatedness Measure for OWL ontologies - Karanastasi, A.; Christodoulakis, S. (2007 Second International Conference on Digital Information Management, 2007)
An effect of the growing importance of the semantic Web used for sharing knowledge over the Internet was the development and publishing of many ontologies in different domains. This led to the need of developing mechanisms for capturing the semantics of the ontologies. In this paper, we introduce the OntoNL semantic relatedness measure, a fully automated way of measuring, in an asymmetric way, semantic relatedness between concepts of domain ontologies. We have developed metrics to guide the automation of the procedure by using feedback from an extensive evaluation with human subjects.